THE CONCEPT AND LEGAL FRAMEWORK FOR PREVENTING CORRUPTION RISKS IN CRIMINAL PROCEEDINGS BEFORE COURTS OF FIRST INSTANCE - Khudoyberdiyev, Hasan (Oriental Journal of History, Politics and Law, 2026)
This article examines the concept of corruption risks arising in criminal proceedings before courts of first instance and the essence of their prevention. It also analyzes the legal framework for preventing corruption risks that may arise during the adjudication of criminal cases in courts of first instance.